2018
DOI: 10.1101/350629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The transferable resistome of produce

Abstract: 25Produce is increasingly recognized as a reservoir of human pathogens and transferable 26 antibiotic resistance genes. This study aimed to explore methods to characterize the 27 transferable resistome of bacteria associated with produce. Mixed salad, arugula, and 28 cilantro purchased from supermarkets were analyzed by means of cultivation-and DNA-29 based methods. Before and after a nonselective enrichment step, tetracycline (tet) 30 resistant Escherichia coli were isolated and plasmids conferring tet res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…IncP-1, a common environmental plasmid group, is largely known for its efficient conjugative transferability potential and stable replication in a wide range of Gram-negative bacteria (Heuer et al, 2012). Conversely, plasmids IncF (Villa et al, 2010), IncI (Blau et al, 2018), and IncQ (Rawlings and Tietze, 2001) show a narrower host range. These plasmids are assumed to be important for the dissemination of ARG in Escherichia coli and other Enterobacteriaceae (Johnson and Nolan, 2009;Suzuki et al, 2010;Heuer et al, 2012;Van Houdt et al, 2013).…”
Section: The Dissemination Mechanisms Of Environmental Resistomementioning
confidence: 99%
See 2 more Smart Citations
“…IncP-1, a common environmental plasmid group, is largely known for its efficient conjugative transferability potential and stable replication in a wide range of Gram-negative bacteria (Heuer et al, 2012). Conversely, plasmids IncF (Villa et al, 2010), IncI (Blau et al, 2018), and IncQ (Rawlings and Tietze, 2001) show a narrower host range. These plasmids are assumed to be important for the dissemination of ARG in Escherichia coli and other Enterobacteriaceae (Johnson and Nolan, 2009;Suzuki et al, 2010;Heuer et al, 2012;Van Houdt et al, 2013).…”
Section: The Dissemination Mechanisms Of Environmental Resistomementioning
confidence: 99%
“…Exogenous plasmid isolation techniques (Bale et al, 1988) clarified how plasmids diffuse in different environments. Recently, plasmids from municipal sewage sludge and recipient bacteria were analyzed for their transferability by exogenous isolation (Blau et al, 2018;Wolters et al, 2018). Referring to pig manure samples, four IncQ-like plasmids were isolated in recipient strains: Pseudomonas putida UWC1, Acinetobacter sp., Ralstonia eutropha, Agrobacterium tumefaciens, and E. coli.…”
Section: Different Approaches To Resistome Profiling Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The blaTEM gene may have been ingested by the donor (e.g. fresh produce) (Blau et al, 2018), and its occurrence in the gut microbiota of healthy individuals, even if never exposed to antibiotics, has been reported (Fouhy et al, 2014;Sommer et al, 2009). In general, the vanA gene abundance (per gram of dry weight) did not vary significantly from T0 to T7, with average measurements at T0 and T7 of 5.87 ± 0.11 and 5.79 ± 0.15 log-units under aerobic conditions, and 7.34 ± 1.17 and 7.17 ± 1.12 log-units under anaerobic conditions (Figure 2).…”
Section: Heterotrophic and Enterobacteria Counts Presented Similar Vamentioning
confidence: 99%
“…Indeed, several recent studies have shown the presence of ARB and ARGs in raw-eaten products (e.g. lettuce), raising concerns for consumers, particularly for immunocompromised people (Araujo et al, 2017;Blau et al, 2018;O'Flaherty et al, 2019;Zhang et al, 2017;Zhu et al, 2017). However, even after ingestion, the success of allochthonous bacteria in the intestinal tract is supposedly antagonized by the gut microbiota, a complex and dynamic community of microorganisms colonizing the gastrointestinal tract of humans since birth (Donaldson et al, 2016;Gibson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%